Website-Based Learning: Optimizing Students’ Numeracy Skills - Puji Lestari; Nabila Nurhaliza Ali (Edumatika, 2023)
The evaluation of the Independent Curriculum (Kurikulum Merdeka) is currently underway, employing various methods such as the Minimum Competency Assessment (Asesmen Kompetensi Minimum [AKM]). AKM assesses general yet fundamental competencies, including numeracy skills. This assessment method endeavors to delineate students' numeracy skills within the context of website-based learning. Employing a descriptive qualitative method, the study involves 20 eighth-grade students from a Junior High School in Ciamis, West Java, Indonesia. Students are instructed to access a website developed by the researchers, featuring study materials and example problems. Throughout the learning activities, students utilize the Google Meet video conferencing application, activating their cameras for interactive sessions. Following the lesson, students undergo a numeracy skills test comprising validated questions. The research outcomes unveil three distinct levels of numeracy skills among students: high, medium, and low. Those with high-level numeracy skills demonstrate proficiency in mathematical numeracy skills indicators but exhibit errors in applying formulas. Conversely, students with moderate and low mathematical numeracy skills commonly struggle with concept comprehension, identifying relevant formulas, and making calculation errors.